Determinants Of the Financial Result of Polish Banks During The COVID-19 Pandemic: The Case of Bank PKO BP SA And Santander Bank SA - Agnieszka WOJCIK-MAZUR (Communications of International Proceedings, 2023)
During the COVID-19 pandemic, the Polish banking sector generated negative profitability ratios. The main aim of the study was to identify the group of factors that have the greatest impact on profitability. Based on the findings, it was indicated that the main determinants included non-economic factors related to the need to make provisions for mortgage loans granted in CHF, accompanied by the lack of statutory regulations of this legal risk. The group of these determinants consists of the applicable tax burden imposed by Polish legislation. Furthermore, it is also important to highlight the negative effects of the pandemic that force the creation of reserves and taxes from other financial institutions significantly increasing business costs and the change in the interest rate policy of the National Bank of Poland (NBP).
Keywords: bank; determinants of financial result; Covid-19